Terapi Zink Oral pada Vitiligo - Eka Devinta Novi Diana; Muhammad Eko Irawanto (MEDICINUS, 2023)
Background: World Health Organization (WHO) estimates that 2 billion people in the world have zinc deficiency. Clinical manifestation of zinc deficiency includes immune system dysfunction, increase of oxidative stress, and release of proinflammatory cytokines. Oxidative stress is one of main factors that plays important role in various autoimmune diseases such as vitiligo. Discussion: Vitiligo is the most common depigmentation disease caused by melanocyte damages which characterized by depigmentation macule or patch on the skin or mucous membranes. Treatment of vitiligo is still considered a challenge, and various treatment modalities show varying results. Zinc is a micronutrient and antioxidant that posseses antiapoptotic activity by influencing melanogenesis and eliminating free radicals. Conclusion: Zinc inhibits oxidative stress and prevent melanocyte damage so it can bd considered as an adjuvant treatment for vitiligo.